Biological rhythms of physiological processes of 1—2 year students (Experimental biology, 2015)
We have investigated biological rhythms of Medical University student’s some indexes of cardiovascular andrespiratory systems, indexes of higher nervous activity, absolute muscle strength during the day, the week, season of theyear. The novelty of the research: biorhythms students revealed the presence of circanual rhythms and the absence ofpronounced ultrdian and infradian hesitations of cardio- vascular system’ indexes. Study of variations of physiologicalfunctions during the day, the week has shown that in most cases revealed changes indexes of higher nervous activityassociated with shortening of sleep’s phase and lengthening of wakefulness’s phase of «day-night» cycle (biologicalrhythm). The discrepancy between of an acrophases of indexes of cardiovascular system is connected with simultaneousinfluence of social factors
Keywords: unequal schedule for different groups of students; various conditions of work; rest and diet of students.